Blocking AGE-RAGE Signaling Improved Functional Disorders of Macrophages in Diabetic Wound. (8th October 2017) - Wang, Qi; Zhu, Guanya; Cao, Xiaozan; Dong, Jiaoyun; Song, Fei; Niu, Yiwen
Abstract : Advanced glycosylation end products (AGEs) accumulate in diabetic wounds. Interactions between AGEs and their receptor (RAGE) leads to dermatologic problems in diabetes. Macrophage, which plays important roles in wound healing, highly expresses RAGE. Therefore, we investigated whether RAGE-expressing macrophages might be responsible for impaired wound healing on diabetes. We used anti-RAGE antibody applied topically on diabetic wounds. After confirming that wound healing was improved in anti-RAGE antibody group compared with normal mice, our results showed that macrophages appeared insufficient in the early stage and fading away slowly in the later proliferative phase compared with the control group, which was ameliorated in anti-RAGE antibody-applied wounds. Blocking AGE-RAGE signaling also increased neutrophils phagocytized by macrophages and promoted the phenotypic switch of macrophages from proinflammatory to prohealing activities. In vitro, phagocytosis of THP-1 (M0) and lipopolysaccharide- (LPS-) induced (M1) macrophages was impaired by treatment with AGEs, while IL-4- and IL-13-induced (M2) macrophages was not. Finally, AGEs increased the proinflammatory response of M1 macrophages, while inhibiting the polarization and anti-inflammatory functions of M2 macrophages. In conclusion, inhibition of AGE-RAGE signaling improved functional disorders of macrophages in the early inflammatory phase, which promoted the healing of wounds in diabetic mice.